Characteristics of patients with acute limb ischemia (ALI) at Hasan Sadikin General Hospital, Bandung, Indonesia in 2019-2020 - Hendri Bayu Nugroho; Teguh Marfen Djajakusumah (Indonesian Vascular Access Association (IVAA), 2022)
Methods: The type of this research is descriptive cross-sectional research. The data was from the medical records of ALI patients who came to Hasan Sadikin Hospital from January 1st, 2019 to December 31, 2020. The data obtained were then identified according to patient gender, patient age, chief complaint, degree, comorbidities, and onset. The data were analyzed descriptively using SPSS ver.17. Results: Of the 99 patients with ALI, it was found the prevalence of men (58%) was higher rather than women (42%) with the largest age distribution around 49-56 years old(23 %). The main complaint of ALI in the emergency ward was pain (32%). Category of ALI based on Rutherford classification was mostly category III (36%). The most common accompanying comorbidities were diabetes in 47 patients (47.47%). Conclusion: Characteristics of ALI in the emergency department of Hasan Sadikin Hospital Bandung mostly occur in men. The degree of ALI according to the Rutherford classification was category III with diabetic comorbidity.